Greasy Raw Wool for Clean-up Process of Marine Oil Spill: from Laboratory Test to Scaled Prototype - M. Periolatto; G. Gozzelino (Chemical Engineering Transactions, 2015)
Greasy raw wool, as sheared, was proposed as natural, cost effective adsorbent material for oil recovery and remediation of marine surface contaminated by oil spills. In this way, an effective cleaning of sea surface can be coupled with the revaluation of a sheep breeding waste, suitable for the purpose thanks to its oilphilic behaviour. A characterization of wools of different origin was carried out by sorption test of IFO 380 oil, either pure or mixed with Diesel, layered on a water surface. The wool has been characterized in terms of humidity, lipids, adherent and not adherent dirt while viscosity, density and surface tension were evaluated for the different oil mixes. Preliminary tests on the process efficiency, performed with reduced volumes of water and oil in a static system, assessed the sorption kinetics, the yield of the process for fresh wool and the number of sorption- regeneration cycles at which the wool can be submitted without reduction of the original adsorption properties. The obtained results were used to set a scaled up series of tests, on a pilot prototype, suitable for reproduce the real recovery conditions of a ship on the sea. The possible destination of the exhausted wool was also taken into account. The obtained results suggest that wool wastes can be a suitable sorbent material for spilled oil recovery on marine surfaces, with performance that are competitive with the materials of synthetic origin proposed for similar applications.